Demarcating day-light-length from temperature effects in PGMS rice using back tracking method. - Njiruh, Nthakanio P.; Qingzhong, Xue (My University, 2014)
Two near isogenic rice lines ZAU11S106 (Photoperiod sensitive genic male sterile) and ZAU11F121(a ZAU11S106 whose PGMS gene has undergone reverse mutation to become a non-PGMS) were used. These two lines were studied to define the effects of temperature and day light length on PGMS gene expression using forward gene expression tracking method. In this method, ZAU11S106 and ZAU11F121 were divided into 8blocks into which they were grown up to mordial stage. This was a growth stage before the pollen matured to become fertile or sterile, a point called critical sterility point (CSP). At this growth stage, the first block was exposed to short day light length (SDLL) treatment. After four (4) days first and second row were put under SDLL treatment. A row was included under the treatment after every four days till the first row headed after which the treatment was withdrawn and all rice allowed to grow up to maturity under long day light length (LDLL) and high temperature growth conditions. The PGMS grown under long day and high temperature growth conditions had higher spikelet sterility than those grown under influence of long daylight length and lower temperature growth conditions. Thus, high temperatures complement photoperiod in inducing sterility in PGMS rice.
Keywords: Critical Sterility Point; PGMS gene; Rice; Forward tracking; Short day